2016
DOI: 10.1007/s00066-016-0943-6
|View full text |Cite
|
Sign up to set email alerts
|

Setup accuracy for prone and supine whole breast irradiation

Abstract: In this series, setup accuracy is significantly worse in prone compared to supine position for the LA and LO directions. However, without proper image-guidance, uncertainty margins of about 1 cm are also necessary for supine WBI. For patients with a higher BMI, larger margins are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 32 publications
6
47
0
Order By: Relevance
“…The population systematic and random errors achieved by Sagittilt © were comparable to studies with daily CBCT verification [13,14,16,[21][22][23][24] (Table 2). Notably, the direction of the largest margin varied across these published data.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The population systematic and random errors achieved by Sagittilt © were comparable to studies with daily CBCT verification [13,14,16,[21][22][23][24] (Table 2). Notably, the direction of the largest margin varied across these published data.…”
Section: Discussionsupporting
confidence: 58%
“…Prone treatments would require more than 10 mm CTV-PTV margin at least in one direction, while for supine it is consistently less than 10 mm in each direction [5,14,23]. Factors which may influence set-up errors included system type, platform design (flat/tilted), set-up technique (breast-torso-oriented), set-up verification (EPID/CBCT), CBCT registration method (clip and/or chest wall), learning curve, study design and patient related factors (body mass index) [14,16,21,23,24]. Despite the heterogeneity of the above mentioned factors in the previous studies, the achieved reproducibility remained more or less the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTV contouring depends on repositioning accuracy and the method of treatment verification. Interfractional differences may be especially large in the prone position [18,30]. Lakosi et al found population systematic error values of 4.5/3.9/3.3 mm in the lateral/longitudinal/vertical directions, while the random error was 5.4/3.8/2.8 mm [27].…”
Section: Gyheartmentioning
confidence: 99%
“…PTV contouring depends on repositioning accuracy and the method of treatment verification. Interfractional differences may be especially large in the prone position[13,66]. Lakosi et al found population systematic error values of 4.5/3.9/3.3 mm in the lateral/longitudinal/vertical directions, while the random error was 5.4/3.8/2.8 mm[15].…”
mentioning
confidence: 99%